The current knowledge and future direction into a new era of eccentric training, a delphi study - Handford, M.; Bright, T.; Mundy, P.; Lake, J.; Theis, N.; Suchomel, T.; Hughes, J. (International Journal of Strength and Conditioning, 2025)
The purpose of the study was to gain a consensus surrounding specific topics concerning eccentric muscle actions and training. Twelve leading researchers and practitioners agreed to conduct the study, of which eleven completed both rounds of the Delphi study. Statements consisted of: defining eccentric training (Question 1) and eccentric overload Question 4), a new construct of time in action, and finally how would they describe an eccentric muscle action. Both a consensus was reached for eccentric training definition: Eccentric training consists of training methods that incorporate just the eccentric phase, or the manipulation of eccentric actions or training with an eccentric emphasis during resistance or plyometric-based training that have two or more contractile phases (concentric, eccentric, isometric), and a classification to muscle lengthening actions consisting of a passive lengthening action, and an active and forced eccentric action (75%). A consensus was reached of a new term of time in action describing the duration of a phase or movement (100%). Finally, a consensus was not reached for a definition of eccentric overload (64%), and that if the term is used researchers are encouraged to define eccentric overload. Future research now needs to assess these concepts on a wider population and for research to investigate some of the concepts raised from the current study.